Characterization of degenerative human facet joints and facet joint capsular tissues. Issue 12 (December 2015) - Kim, J.-S.; Ali, M.H.; Wydra, F.; Li, X.; Hamilton, J.L.; An, H.S.; Cs-Szabo, G.; Andrews, S.; Moric, M.; Xiao, G.; Wang, J.H.-C.; Chen, Di; et al.
Summary: Objective: Lumbar facet joint degeneration (FJD) may be an important cause of low back pain (LBP) and sciatica. The goal of this study was to characterize cellular alterations of inflammatory factor expression and neovascularization in human degenerative facet joint capsular (FJC) tissue. These alterations in FJC tissues in pain stimulation were also assessed. Design: FJs were obtained from consented patients undergoing spinal reconstruction surgery and cadaveric donors with no history of back pain. Histological analyses of the FJs were performed. Cytokine antibody array and quantitative real-time polymerase chain reaction (qPCR) were used to determine the production of inflammatory cytokines, and western blotting analyses (WB) were used to assay for cartilage-degrading enzymes and pain mediators. Ex vivo rat dorsal root ganglion (DRG) co-culture with human FJC tissues was also performed. Results: Increased neovascularization, inflammatory cell infiltration, and pain-related axonal-promoting factors were observed in degenerative FJCs surgically obtained from symptomatic subjects. Increased VEGF, (NGF/TrkA), and sensory neuronal distribution were also detected in degenerative FJC tissues from subjects with LBP. qPCR and WB results demonstrated highly upregulated inflammatory cytokines, pain mediators, and cartilage-degrading enzymes in degenerative FJCs. Results from ex vivo co-culture of the DRG and FJC tissue demonstrated that degenerative FJCs increased the expression of inflammatory pain molecules in the sensory neurons. Conclusion: Degenerative FJCs possess greatly increased inflammatory and angiogenic features, suggesting that these factors play an important role in the progression of FJD and serve as a link between joint degeneration and neurological stimulation of afferent pain fibers.